2020
DOI: 10.1021/acs.chemmater.0c01238
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Two-Dimensional Ostwald Ripening in Semiconductor Nanoplatelets

Abstract: Colloidal semiconductor nanoplatelets are rectangular, quasi-two-dimensional crystallites that are only a few atomic layers thick. In the most heavily studied systems (such as CdE with E = S, Se, or Te), the highly anisotropic nanoplatelet shape forms from an isotropic cubic crystal lattice. This has been difficult to reconcile with standard nanocrystal growth models. Previously, we proposed that nanoplatelets arise due to an intrinsic kinetic instability that enhances growth on narrow crystal facets under sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 55 publications
2
40
0
Order By: Relevance
“…The exposed Cd‐terminated basal facets of colloidal zinc blende CdSe NPLs are composed of structurally identical polar [ 28 ] planes and thus are stabilized by various types of ligands [ 75 ] to assure charge neutrality. Although there are several competing formation mechanisms of CdSe NPLs, including oriented attachment with specific precursors, [ 76,77 ] anisotropic Ostwald ripening of small NPLs, [ 78 ] and kinetic instability caused by insoluble precursors, [ 79 ] the driving force of anisotropic growth for CdSe NPLs with isotropic zinc blende lattice structure is still under debate. However, ligands are believed to play an important role during the anisotropic growth of CdSe NPLs.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
“…The exposed Cd‐terminated basal facets of colloidal zinc blende CdSe NPLs are composed of structurally identical polar [ 28 ] planes and thus are stabilized by various types of ligands [ 75 ] to assure charge neutrality. Although there are several competing formation mechanisms of CdSe NPLs, including oriented attachment with specific precursors, [ 76,77 ] anisotropic Ostwald ripening of small NPLs, [ 78 ] and kinetic instability caused by insoluble precursors, [ 79 ] the driving force of anisotropic growth for CdSe NPLs with isotropic zinc blende lattice structure is still under debate. However, ligands are believed to play an important role during the anisotropic growth of CdSe NPLs.…”
Section: Emission Tunability For Cdse‐based Nplsmentioning
confidence: 99%
“…The fast generation of CdSe monomers from the reaction of bis(acyl) selenides (sulfides) and cadmium carboxylates was previously utilized to form CdSe (CdS) nanoplatelets. 45,46 To assess the importance of highly reactive Se precursors for MSNCs, we repeated our reaction with two less-reactive Se precursors that are often exploited in nanocrystal syntheses, elemental Se and trioctylphosphine selenide (Figure S8). Neither produced MSNCs.…”
Section: Resultsmentioning
confidence: 99%
“…Such a process has already been invoked to explain ripening of CdSe nanoplatelets. 46,51 For the MSNCs, these monomers add to one of the facets of the tetrahedral-shaped particles and complete a layer to form the next bigger size. Note that the addition of a layer to any of the four facets of a tetrahedron results in the next bigger tetrahedron in a series, consistent with MSNC growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gao et al reported the formation of hollow bundle-shaped NaYF 4 microparticles, where multi-stage shape evolution occurred due to Ostwald ripening [ 53 ]. Furthermore, Knusel et al showed that two-dimensional materials with tunable thickness could be produced due to this effect [ 54 ]. Zhang and Wang have also demonstrated that complex shell-in-shell morphologies can be obtained through this process [ 55 ].…”
Section: Main Mechanisms Of Nanoparticle Shape Controlmentioning
confidence: 99%